2011
DOI: 10.5902/217976922479
|View full text |Cite
|
Sign up to set email alerts
|

Perfil dos doadores e não doadores de sangue de um município do sul do Brasil

Abstract: Este estudo delineou o perfil dos doadores e não doadores de sangue de uma cidade do Sul do Brasil. Trata-se de um estudo transversal, com abordagem quantitativa. Os dados foram obtidos através de formulários com amostra de 236 estudantes universitários e de 152 usuários que acessaram o pronto atendimento do hospital da mesma cidade, totalizando 388 indivíduos. O instrumento foi aplicado no mês de outubro de 2008, sendo obtidos dados como: sexo, escolaridade, idade, e, se eram ou não doadores de sangue. Questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 8 publications
1
4
0
8
Order By: Relevance
“…Pereira et al (2016) highlight the general impact of the lack of information and trust in health institutions in Brazil. Lack of information as a barrier to donation is reported in studies from countries of the Americas and the Caribbean (Belato et al, 2011;García Gutiérrez, Sáenz de Tejada, & Cruz, 2003;Gillespie & Hillyer, 2002). The assumptions agree with the participants' answers in this study that the less favored populations have lower confidence in institutions (R.M.G.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Pereira et al (2016) highlight the general impact of the lack of information and trust in health institutions in Brazil. Lack of information as a barrier to donation is reported in studies from countries of the Americas and the Caribbean (Belato et al, 2011;García Gutiérrez, Sáenz de Tejada, & Cruz, 2003;Gillespie & Hillyer, 2002). The assumptions agree with the participants' answers in this study that the less favored populations have lower confidence in institutions (R.M.G.…”
Section: Discussionsupporting
confidence: 87%
“…Some participants also highlighted the unexplored potential of low income and education donors. Besides the record that the profile of donors in Brazilian blood centers tends to have a higher income and schooling and to be generally formed by young men (Belato, Weiller, Oliveira, Brum, & Schimith, 2011;Liberato et al, 2013;Zago et al, 2010), no study in Brazil investigated the reasons for the low participation of populations with lower income and schooling in blood banks. Pereira et al (2016) highlight the general impact of the lack of information and trust in health institutions in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Different from these research, Belato et al. 29 research revealed that 50% of donors were women, and 50% were men.…”
Section: Resultsmentioning
confidence: 89%
“…O presente estudo constatou que, na presente amostra, o percentual de doadores mulheres foi maior que o de homens, achado condizente com outros estudos 10,11 . Contrapondo esses resultados, outros estudos [12][13][14][15][16][17] observaram prevalência maior de doadores do sexo masculino, que pode ser explicada pelo fato de mulheres serem mais susceptíveis a anemias que os homens, pois precisam de mais ferro na vida reprodutiva 18 ou devido à hipotensão arterial sistólica ou diastólica 19 .…”
Section: Discussionunclassified